Peningkatan kualitas hidup lansia melalui skrining risiko morbiditas dan sosialisasi penerapan pola makan sehat - Ardesy Melizah Kurniati; Nur Riviati; Syarif Husin; Syifa Alkaf (Fakultas Kedokteran Universitas Sriwijaya, 2020)
Improving the quality of life of the elderly through screening for risk of morbidity and promote the healthy eating practices. Aging results physiological decline in the organ function. Quality of life can be further decreased if there are other diseases that aggravate the health condition of the elderly. Chronic diseases such as diabetes and cardiovascular disease are the causes of disability in the elderly. Diet and physical activity are factors that can prevent this morbidity. Morbidity screening and education of healthy eating patterns are still needed for elderly, who are physically active, to support their health. Community service activities consist of nutrition counseling for elderly and health checking such as examine waist circumference, body fat mass, blood pressure, cholesterol and random blood sugar test. A total of fifty elderly, aged sixty years and over, that consist of forty-two women and eight men from the elderly community at Central General Hospital. Dr. Mohammad Hoesin Palembang, was included in this activity. The mean proportion of body fat mass was 35.01% + 9.03. As many as 6 (75%) men and 35 (83.3%) women had waist circumference exceeding normal. There were 2 people (4%) who had blood sugar levels> 200 g / dL, 18 people (36%) with cholesterol levels> 200 g / dL, and 12 people (24%) with blood pressure> 150/90 mmHg. Most of the elderly have central obesity and high cholesterol levels. There are participants who should receive therapy for having high blood sugar, cholesterol, and blood pressure. Respondents who have risk of disease are advised to carry out further examinations. A dietary assistance program could be proposed to improve obesity conditions in future community service activities.